2011
DOI: 10.1037/a0021158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a brief video intervention on White university students' racial attitudes.

Abstract: The authors investigated the effects of a brief video intervention on the racial attitudes of White university students. One hundred thirty-eight self-identified White students were randomly assigned to either an experimental condition in which they viewed a video documenting the pervasiveness of institutional racism and White privilege in the United States or a neutral control condition. Findings offer preliminary support that participants in the experimental, but not the control, condition showed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 44 publications
7
64
0
2
Order By: Relevance
“…Perhaps the exposure to racial diversity during the first year provided a critical incident that infiuenced levels of White guilt. This upward trend in guilt following exposure is consistent with research that documented how hrief exposure to a video about institutional racism and White privilege significantly increased White guilt immediately following the video (Soble, Spanierman, & Liao, 2011). Thus, our results extend those noted above to suggest that attending college may have a prolonged effect on White guilt over a longer period of time.…”
Section: White Guiltsupporting
confidence: 92%
“…Perhaps the exposure to racial diversity during the first year provided a critical incident that infiuenced levels of White guilt. This upward trend in guilt following exposure is consistent with research that documented how hrief exposure to a video about institutional racism and White privilege significantly increased White guilt immediately following the video (Soble, Spanierman, & Liao, 2011). Thus, our results extend those noted above to suggest that attending college may have a prolonged effect on White guilt over a longer period of time.…”
Section: White Guiltsupporting
confidence: 92%
“…However, there were no significant changes in explicit racial attitudes or motivations to respond without bias. Similarly, Soble et al (2011) found among a sample of White college students that providing a brief video intervention on institutional racism and White privilege produced significant increases in racial awareness and empathy. However, no significant changes were found in regard to attitudes related to personal closeness and comfort with racial diversity in one’s own life or racial prejudice.…”
Section: Discussionmentioning
confidence: 94%
“…However, no significant changes were found in regard to attitudes related to personal closeness and comfort with racial diversity in one’s own life or racial prejudice. As posited by Soble et al (2011), the lack of change in closeness and response to biases may be enhanced through inclusion of interracial contact which provides opportunities to interact and dialogue with individuals of different racial backgrounds and motivate change in behavior.…”
Section: Discussionmentioning
confidence: 99%
“…the transgender concept, what is often a lifelong pattern of gender atypicality among persons who may identify as transgender, how an organic progression of transgenderism affects family systems) in a medium that would not be perceived as threatening, hyperbolic, or politically biased. Prior studies have included audio or visual media materials as experimental stimuli because they meet these criteria (Chaiken and Eagly 1983;Christie and Collyer 2008;Furnham, De-Siena, and Gunter 2002;Soble, Spanierman, and Liao 2011;Walters 1994). A television news show filmed and distributed in the USA dedicated a one-hour news programme to transgenderism.…”
Section: Methodsmentioning
confidence: 99%